The Development of Amusement Parks in Thailand - O-ourd, Nathaporn; Anantsuksomsri, Sutee (Journal of Architectural/Planning Research and Studies (JARS), 2021)
This article aims to illustrate the development of amusement park business and agglomeration patterns of amusement park locations in Thailand from the past to the present. From literature reviews and geographical analysis, the study finds that the first amusement park in Thailand was established in 1973. In the first decade of the amusement park business, there was a cluster of amusement parks only in big cities. During the 1997 financial crisis, many amusement parks faced problems in business operations, and some of them had to close their businesses. Later, in 2007, the business has recovered. Currently, amusement park businesses are operating in both primary and secondary cities in every region. In addition to amusement parks with mechanical rides, many amusement parks with water play areas (waterparks) have operated their businesses around the country. The study also finds that there are obvious clusters of the amusement park business in the Bangkok Metropolitan Region, Phetchaburi - Prachuap Khiri Khan, and Chonburi. The agglomerations are dense in the provinces with significant tourism.